Markerless 3D motion capture for animal locomotion studies - Sellers, William Irvin (The Company of Biologists, 2014)
Obtaining quantitative data describing the movements of animals is an essential step in understanding their locomotor biology. Outside the laboratory, measuring animal locomotion often relies on video-based approaches and analysis is hampered because of difficulties in calibration and often the limited availability of possible camera positions. It is also usually restricted to two dimensions, which is often an undesirable over-simplification given the essentially three-dimensional nature of many locomotor performances. In this paper we demonstrate a fully three-dimensional approach based on 3D photogrammetric reconstruction using multiple, synchronised video cameras. This approach allows full calibration based on the separation of the individual cameras and will work fully automatically with completely unmarked and undisturbed animals. As such it has the potential to revolutionise work carried out on free-ranging animals in sanctuaries and zoological gardens where ad hoc approaches are essential and access within enclosures often severely restricted. The paper demonstrates the effectiveness of video-based 3D photogrammetry with examples from primates and birds, as well as discussing the current limitations of this technique and illustrating the accuracies that can be obtained. All the software required is open source so this can be a very cost effective approach and provides a methodology of obtaining data in situations where other approaches would be completely ineffective.